Telencephalic stab wound injury induces regenerative angiogenesis and neurogenesis in zebrafish: unveiling the role of vascular endothelial growth factor signaling and microglia - Danielle Fernezelian; Philippe Rondeau; Laura Gence; Nicolas Diotel (Neural Regeneration Research)
After brain damage, regenerative angiogenesis and neurogenesis have been shown to occur simultaneously in mammals, suggesting a close link between these processes. However, the mechanisms by which these processes interact are not well understood. In this work, we aimed to study the correlation between angiogenesis and neurogenesis after a telencephalic stab wound injury. To this end, we used zebrafish as a relevant model of neuroplasticity and brain repair mechanisms. First, using the Tg(fli1:EGFP × mpeg1.1:mCherry) zebrafish line, which enables visualization of blood vessels and microglia respectively, we analyzed regenerative angiogenesis from 1 to 21 days post-lesion. In parallel, we monitored brain cell proliferation in neurogenic niches localized in the ventricular zone by using immunohistochemistry. We found that after brain damage, the blood vessel area and width as well as expression of the fli1 transgene and vascular endothelial growth factor (vegfaa and vegfbb) were increased. At the same time, neural stem cell proliferation was also increased, peaking between 3 and 5 days post-lesion in a manner similar to angiogenesis, along with the recruitment of microglia. Then, through pharmacological manipulation by injecting an anti-angiogenic drug (Tivozanib) or Vegf at the lesion site, we demonstrated that blocking or activating Vegf signaling modulated both angiogenic and neurogenic processes, as well as microglial recruitment. Finally, we showed that inhibition of microglia by clodronate-containing liposome injection or dexamethasone treatment impairs regenerative neurogenesis, as previously described, as well as injury-induced angiogenesis. In conclusion, we have described regenerative angiogenesis in zebrafish for the first time and have highlighted the role of inflammation in this process. In addition, we have shown that both angiogenesis and neurogenesis are involved in brain repair and that microglia and inflammation-dependent mechanisms activated by Vegf signaling are important contributors to these processes. This study paves the way for a better understanding of the effect of Vegf on microglia and for studies aimed at promoting angiogenesis to improve brain plasticity after brain injury.